TRANSLATIONAL CREATIVITY: TRANSLATING GENRE CONVENTIONS IN STATUTES - Nielsen, Sandro (Vertimo studijos, 2017)
A long-established approach to legal translation focuses on terminological equivalence making translators strictly follow the words of source texts. Recent research suggests that there is room for some creativity allowing translators to deviate from the source texts. However, little attention is given to genre conventions in source texts and the ways in which they can best be translated. I propose that translators of statutes with an informative function in expert-to-expert communication may be allowed limited translational creativity when translating specific types of genre convention. This creativity is a result of translators adopting either a source-language or a targetlanguage oriented strategy and is limited by the pragmatic principle of co-operation. Examples of translation options are provided illustrating the different results in target texts. The use of a target-language oriented strategy leads to target texts that contain genre conventions expected by the target audience and at the same time retain the substantive legal contents of source texts. This, I argue, results in translations that are both factually and conventionally correct seen from the point of view of the intended target audience.